THE EURASIAN ECONOMIC UNION: DEVELOPMENT PROSPECTS - MALYSHEV, Dmitri (CENTRAL ASIA AND THE CAUCASUS, 2015)
The integration unions that have emerged in the post-Soviet region can guarantee its states preservation of their sovereignty, as well as the opportunity to oppose various internal and external threats, challenges, and risks. Kazakhstan and Russia have become the driving forces behind the integration processes in post-Soviet Eurasia, and these two countries bear the responsibility for maintaining stability in the region. The Customs Union and Common Economic Space formed a platform for launching post-Soviet Eurasia to a higher level of integration—the Eurasian Economic Union (EEU), which has been functioning since 1 January 2015 as “an international organization of regional economic integration with international legal standing.” The EEU is intended for transforming the post-Soviet region into a new, more influential target of geopolitics in the future, a union that is qualitatively different to the CIS. The very fact that the EEU exists is undoubtedly an important achievement in integration development in the post-Soviet region. Functioning of the union should lead to an increase in goods turnover, a rise in domestic and foreign investments, and significant economic growth. Experts also see certain prospects for reorienting the economy of the regional states from a primarily raw material model to high-tech sectors. In addition, certain countries should receive benefits. The EEU is faced with the difficult task of competing with alternative projects unfolding in the post-Soviet region: America’s New Silk Road program, which places China and Russia outside regional economy and policy; America’s Trans-Pacific Partnership project, which, according to the intentions of its creators, should become an alternative to Asia Pacific Economic Cooperation (APEC), where China holds a relatively strong position; the Turkic project advanced by Turkey and Kazakhstan; and, finally, the Great Silk Road Economic Belt regional trade and transport project launched by the PRC in 2013. Keeping in mind that the participating states and goals of this project partially coincide with the EEU’s precepts, they could reciprocate each other and render mutual assistance, drawing up for Russia, the Central Asian and Caucasian states a strategy for responding to internal and external challenges and risks. The Shanghai Cooperation Organization (SCO) continues to be an important lever of influence in the APR and Central Asia, giving Russia a unique opportunity to discuss with China many pressing international problems. Creation of the CU and EEU is, in itself, not enough for full-fledged Eurasian integration. So it is important to encourage such measures as forming a common market in Eurasia and expanding opportunities for mutually advantageous business relations both with individual states beyond the post-Soviet region and on a multilateral basis with other integration unions and organizations. In the new geopolitical conditions, it is important to establish pragmatic relations in Eurasia on an equal basis. This will guarantee stability for the participants in the integration processes.